2011
DOI: 10.5688/ajpe75117
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Publication Productivity Among Hospital Pharmacists in France and Quebec

Abstract: Objective. To describe publications by hospital pharmacists in France and Quebec and evaluate factors predictive of publication productivity. Method. Variables related to scientific publication productivity were identified through a search of the literature and organized into 4 themes (ie, personal and professional characteristics, hospital activities, research and publishing activities, publication-related motivations and perceptions). A questionnaire was developed that included short-answer items and 58 mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 16 publications
0
18
1
Order By: Relevance
“…[3][4][5] This association appears to correlate with the number of successful grant applications and the financial value of the grants. 6 The quality of the investigators A number of factors have been associated with the research productivity of individuals.…”
Section: Funding Of Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…[3][4][5] This association appears to correlate with the number of successful grant applications and the financial value of the grants. 6 The quality of the investigators A number of factors have been associated with the research productivity of individuals.…”
Section: Funding Of Researchmentioning
confidence: 99%
“…It has been shown that the most productive individuals have associated academic duties and protected research time. 4 The degree of productivity correlates with the amount of time that is allocated for research. 4,7 Conversely, an increasing clinical workload has either a nonsignificant 8 or significant negative correlation with research productivity.…”
Section: Funding Of Researchmentioning
confidence: 99%
See 3 more Smart Citations